79 Outcomes of Collagenase Clostridium Histolyticum in Men with Congenital Penile Curvature. Issue 1 (1st April 2022) - Burgon, H; Tyler, A; Green, B; Savage, J; Brearton, K; Granberg, C; Ziegelmann, M; Kohler, T; Helo, S; Trost, L
ABSTRACT: Introduction: Congenital penile curvature is a relatively uncommon condition characterized by penile angulation. Similar to Peyronie's Disease (PD), this condition has historically been managed with various surgical techniques. Given the efficacy of Collagenase Clostridium Histolyticum (CCH) in men with PD, our team has elected to treat men with CPD with CCH injections. Objective: To describe outcomes of CPD men treated with CCH injections and to compare against a traditional PD cohort. Methods: A prospective database has been maintained of all men undergoing CCH injections by our team since Jan 2014. The specific CCH administration protocol has been modified over time and currently includes combined use of RestoreX traction therapy, sildenafil, 0.9 mg of CCH diluted into 0.7 ml, injections performed at the point of maximal curvature, and aggressive manual modeling. Curvatures were measured in two planes (dorsal and lateral), with the combined measure reported as a composite. Outcomes were reported based on the most recent curvature assessment obtained minus baseline. Men were included if they received at least one series of CCH injections and had at least one baseline and follow-up curvature assessment available. Results: A total of 272 men comprised the current cohort, with 23 exhibiting CPD and 249 PD. Mean age was higher in PD men (57.4 vs 38.4, p<0.0001), and mean PD duration was 18 months in PD men. Median baseline curvature was non-statistically higher in PD (65 vs 55 degrees, p=0.06). Baseline curvature directions for PD and CPD, respectively were: dorsal (82% vs 35%, p<0.0001), lateral (58% vs 78%, p<0.05), ventral (11% vs 35%, p<0.01). Following treatment with CCH, median curvature improvement was similar between cohorts, with 20 degrees (IQR 5, 35) for PD and 20 degrees (IQR 5, 30) for CPD, p=0.62. Percentage improvement from baseline was non-statistically higher in PD men (33% vs 29%, p=0.99). Conclusions: Treatment of CPD men with CCH is a viable therapeutic option and provides similar benefits to those observed in men with PD. Disclosure: No